Uncovering Innovations in Instructional System Design Models for Arabic Language Learning - Nabila; Miftahul Khair; Muhammad Jundi (Al-Madrasah: Jurnal Pendidikan, Pembelajaran dan Kebudayaan, 2024)
This research aims to describe the classification of instructional system design models and examples of their application in Arabic language learning. Data were collected from various scholarly sources including books and journal articles. Instructional system design models proposed by numerous experts are classified into three types: product-oriented instructional system design models, class-oriented instructional system design models, and system-oriented instructional system design models. The instructional design models utilized in Arabic language learning include ASSURE, ADDIE, and Dick & Carey. These design models assist educators and researchers in designing and developing various learning methods and tools to achieve high-quality, effective, and engaging learning experiences.   In conclusion, the proper application of these instructional system design models can significantly enhance the effectiveness and quality of Arabic language instruction. The implications of this study suggest that a systematic approach to instructional design is crucial for achieving educational goals. It is recommended that educators and curriculum developers integrate these models into their instructional strategies to foster improved learning outcomes and student engagement.